Dinâmica espaço temporal da agropecuária no município de Primavera (PA): uma visão para a transição agroecológica - SOUZA, Caio Cezar Ferreira de (2020)
The exploitation of natural resources caused to meet human needs, through the advancement of agriculture, livestock, among others, cause changes in environmental systems in time and space. Thus, the objective of the research is to evaluate the spatio-temporal dynamics of agriculture in the municipality of Primavera from 1980 to 2018 and to identify potentialities for the agroecological transition. The methodology was based on the elaboration of land use and land cover maps in three different periods by means of image processing from the LANDSAT (1984 and 2005) and Sentinel (2018) satellites and from the characterization of the agricultural sector with the use of secondary data on socioeconomic and productive information. The results showed that the municipality of Primavera did not show major changes in terms of land occupation by the agricultural sector, varying between 23.3% and 29.3% of the total area, even after the installation of a large mining enterprise in the city. In addition, when analyzing the agricultural sector it was possible to notice that the technological level and agricultural diversification are low, with little use of agrochemicals and machinery and the predominance of the cultivation of only five agricultural crops. Therefore, it was possible to realize that despite the low diversification and limited technology, agriculture is fundamental for the municipality of Primavera, especially for small farmers, therefore, it is necessary to seek alternatives to improve agricultural production, which may become viable. through the incorporation of sustainable production systems based on agroecological principles.